Validation of the Modified Fatigue Impact Scale in Mild to Moderate Traumatic Brain Injury. Issue 2 (March 2015) - Schiehser, Dawn M.; Delano-Wood, Lisa; Jak, Amy J.; Matthews, Scott C.; Simmons, Alan N.; Jacobson, Mark W.; Filoteo, J. Vincent; Bondi, Mark W.; Orff, Henry J.; Liu, Lin
Abstract : Objective: To evaluate the validity of the Modified Fatigue Impact Scale (MFIS) in veterans with a history of mild to moderate traumatic brain injury (TBI). Participants: Veterans ( N = 106) with mild (92%) or moderate (8%) TBI. Setting: Veterans Administration Health System. Procedure: Factor structure, internal consistency, convergent validity, sensitivity, and specificity of the MFIS were examined. Results: Principal component analysis identified 2 viable MFIS factors: a Cognitive subscale and a Physical/Activities subscale. Item analysis revealed high internal consistency of the MFIS Total scale and subscale items. Strong convergent validity of the MFIS scales was established with 2 Beck Depression Inventory II fatigue items. Receiver operating characteristic curve analysis revealed good to excellent accuracy of the MFIS in classifying fatigued versus nonfatigued individuals. Conclusion: The MFIS is a valid multidimensional measure that can be used to evaluate the impact of fatigue on cognitive and physical functioning in individuals with mild to moderate TBI. The psychometric properties of the MFIS make it useful for evaluating fatigue and provide the potential for improving research on fatigue in this population.